2019
DOI: 10.1002/lsm.23158
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo and animal study of the blue diode laser, Tm fiber laser, and their combination for laparoscopic partial nephrectomy

Abstract: Background and Objectives To evaluate the feasibility of using a novel blue diode laser (blue laser), a thulium fiber laser (Tm laser), and their combination as a directed‐energy surgical tool in laparoscopic partial nephrectomy (LPN). Study Design/Materials and Methods The blue laser emitting at 442 nm, the Tm laser emitting at 1,940 nm wavelengths, and the combination of them were tested. First, cutting and coagulative abilities of the lasers were characterized ex vivo on porcine kidney in air and CO2. Histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The Hybrid laser's carbonisation was significantly lower than those for TFL (28). Those properties for both TFL and Hybrid laser were observed by Arkhipova et al in their study (29).…”
Section: Thulium Fiber Laser For Soft Tissuessupporting
confidence: 65%
“…The Hybrid laser's carbonisation was significantly lower than those for TFL (28). Those properties for both TFL and Hybrid laser were observed by Arkhipova et al in their study (29).…”
Section: Thulium Fiber Laser For Soft Tissuessupporting
confidence: 65%
“…Thus, the lasers, which emit at wavelengths absorbed highly by hemoglobin, are considered of certain interest for application on vascularized organs. 12,13 According to the wavelength of each laser type, effects can penetrate deeply and have a narrow or a wide ratio of scattering and absorption in soft tissues. The scattering and absorption of the laser beams also depends on type and color of tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental LPN revealed that the blue laser provided fast cutting with minimal carbonization, whereas Tm laser induced slow cutting with strong carbonization. The combination of the blue and Tm lasers provided the most promising results demonstrating the highest resection rate, almost carbonization-free resection surface and clinically acceptable hemostasis enabling LPN without the need for vessel clamping [20 ▪ ]. In the same year Y Wang et al have published study to evaluate the technical feasibility and outcomes of 2-μm continuous thulium LLPN and CLPN in the treatment of patients with SRMs.…”
Section: Laser Laparoscopic and Robotic Partial Nephrectomymentioning
confidence: 99%